Identifikasi Data Reservoir Dengan Menggunakan Pemodelan Software RFD Untuk Mengetahui Production Forecast Rate Di Sumur J Lapangan A - Edy Soesanto; Eko Prastio; Jessica Abidin (Jurnal Bhara Petro Energi, 2024)
Reservoir simulation is a process of mathematically modeling reservoir conditions by integrating various  existing  data  (geology,  geophysics,  petrophysics,  reservoirs,  etc)  to  obtain  reservoir performance  in  well  conditions  so  that  the  purpose  of  reservoir  simulation  is  to  determine  the current  and  future  reservoir  performance  to  estimate  the  rate  of  oil  production  (production forecast  rate).  Rapid  technological  developments  encourage  experts  to  create  computer software  that  is  used  as  a  simulation  tool.  The  method  in  this  study  uses  reservoir  modeling simulation  software.  The  production  forecast  rate  in  this  reservoir  model  is  carried  out  for  2 years  by  only  adding  one  production  well  in  the  reservoir  area  that  has  not  been  drained, namely infill well A. This shows that the oil production rate continues to decrease but increases the cumulative oil production. The cumulative oil production produced by well A was 33,80 STB in  2014  with  an  average  increase  of  12%.  Therefore,  it  is  necessary  to  evaluate  the  reservoir model after 2014 in detail the value of the data again so that the reservoir simulation process for the next forecast gets good oil production results.